2001
DOI: 10.1046/j.1365-2826.2001.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Antenatal Glucocorticoid Treatment Decreases Hypothalamic Corticotropin Releasing Hormone mRNA but not Corticosteroid Receptor mRNA Expression in the Fetal Guinea‐Pig Brain

Abstract: Approximately 10% of pregnant women are treated with synthetic glucocorticoids in late gestation, to promote fetal lung maturation. The effectiveness of this treatment has led to the use of repeated dose regimens, with little knowledge of the impact on neuroendocrine development. Animal studies have recently shown that repeated fetal glucocorticoid exposure can lead to permanent changes in hypothalamic-pituitary-adrenal (HPA) function in offspring. In this study, we hypothesized that such treatment modifies co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 54 publications
3
71
0
Order By: Relevance
“…This is possible since autologous regulation of MR gene expression has been demonstrated previously in the hippocampus of rats (Holmes et al 1995, Kalman & Spencer 2002. Our observations are most consistent with those reported in the guinea pig (Dean et al 2001, McCabe et al 2001 Mean relative mRNA levels of glucocorticoid receptor (GR), mineralocorticoid receptor (MR), 11b-hydroxysteroid dehydrogenase (11bHSD)1, and 11bHSD2 in adult sheep (Cohort 2) grouped according to sex. Data are presented as meanGS.E.M.…”
Section: Effects Of Maternal Betamethasone Injections On Hippocampal supporting
confidence: 90%
“…This is possible since autologous regulation of MR gene expression has been demonstrated previously in the hippocampus of rats (Holmes et al 1995, Kalman & Spencer 2002. Our observations are most consistent with those reported in the guinea pig (Dean et al 2001, McCabe et al 2001 Mean relative mRNA levels of glucocorticoid receptor (GR), mineralocorticoid receptor (MR), 11b-hydroxysteroid dehydrogenase (11bHSD)1, and 11bHSD2 in adult sheep (Cohort 2) grouped according to sex. Data are presented as meanGS.E.M.…”
Section: Effects Of Maternal Betamethasone Injections On Hippocampal supporting
confidence: 90%
“…The maintained increase in fetal plasma ACTH concentrations in the presence of high circulating glucocorticoid near term is paradoxical, as glucocorticoid-negative feedback is known to be operational in the fetus [59][60][61]. Molecular studies of the fetal HPA axis indicate that there is increased central drive at the level of the PVN (CRH and AVP), which in turn leads to increased synthesis and secretion of ACTH from corticotrophs in the anterior pituitary [60,62,63].…”
Section: Hpa Developmentmentioning
confidence: 99%
“…Neurons in the parvocellular division of the hypothalamic paraventricular nuclei (PVN) synthesize both CRH and AVP, or only CRH, and their axons project to the median eminence where the produced neuropeptides are released. Repeated fetal glucocorticoid exposure to synthetic glucocorticoids, dexamethasone or betamethasone, inhibits fetal HPA function, as significantly decreased levels of CRH mRNA in the hypothalamic PVN in both male and female fetuses were established (32). Delay of CRH release in the external zone of the median eminence, shown by immunocytochemistry, might further confirm the decreased synthetic activity of CRH neurons in the fetus and neonatal offspring after fetal Dx exposure (37).…”
Section: Antenatal Treatment and Fetal Hpa Axis Functionmentioning
confidence: 89%
“…Single maternal Dx exposure results in significant increases in MR and GR mRNA in the CA1-2 region of the hippocampus, and MR mRNA in the dentate gyrus in female fetuses, while changes are absent in male guinea pig fetuses (31). After multiple maternal treatment with Dx, marked increases in MR mRNA level in the hippocampus of female fetuses were recorded, while in males enhancement of GR mRNA was shown in limbic structures indicating changed hippocampal feedback sensitivity to glucocorticoids, natural or synthetic (32). Quantitative in situ hybridization demonstrated that the MR mRNA level is transiently decreased after a single Dx injection in the mouse fetus (33).…”
Section: Antenatal Treatment and Fetal Hpa Axis Functionmentioning
confidence: 96%